Toward broadband vibration-based energy harvesting - Tang, Lihua (2014)
The dramatic reduction in power consumption of current integrated circuits has evoked great research interests in harvesting ambient energy, such as vibrations, as a potential power supply for electronic devices to avoid battery replacement. Currently, most vibration-based energy harvesters are designed as linear resonators to achieve optimal performance by matching their resonance frequencies with the ambient excitation frequencies a priori. However, a slight shift of the excitation frequency will cause a dramatic reduction in performance. Unfortunately, in the vast majority of practical cases, the ambient vibrations are frequency-varying or totally random with energy distributed over a wide frequency spectrum. Hence, developing techniques to increase the bandwidth of vibration-based energy harvesters has become the next important problem in energy harvesting. This article reviews the advances made in the past few years on this issue. The broadband vibration-based energy harvesting solutions, covering resonance tuning, multimodal energy harvesting, frequency up-conversion, and techniques exploiting non-linear oscillations, are summarized in detail with regard to their merits and applicability in different circumstances.